2005
DOI: 10.11646/zootaxa910.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Demicryptochironomus Lenz from China (Diptera: Chironomidae)

Abstract: The genus Demicryptochironomus Lenz 1941 from China is revised. The males of six new species are described: D. (Demicryptochironomus) antennarius sp. n., D. (D.) minus sp. n., D. (D.) pannus sp. n., D. (D.) yui sp. n., D. (Irmakia) concavus sp. n., D. (I.) constrictus sp. n. Demicryptochironomus (I.) neglectus Reiss 1988 is new to China. Demicryptochironomus (D.) vulneratus (Zetterstedt 1838) and D. (I.) spatulatus Wang & Zheng 1994 are redescribed. The larva of D. (D.) vulneratus is described from China f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Prior to this study, 19 species of Demicryptochironomus have been reported from the Sino-Indian region: 1 from Nepal, 2 from India, 4 from Japan, 7 from the Russian Far East, and 9 from China (Chaudhuri et al 2001;Makarchenko et al 2005;Reiss 1988;Sasa & Kikuchi 1995;Wang 2000;Wang & Zheng 1994;Yan et al 2005;Yan & Wang 2006). Yan et al (2005) suggested that 5 Japanese species originally placed in the genus Cryptotendipes by Sasa and his co-authors should be transferred to Demicryptochironomus. Yan and Wang (2006) We also re-examined holotypes of the genus Parachironomus from Japan.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Prior to this study, 19 species of Demicryptochironomus have been reported from the Sino-Indian region: 1 from Nepal, 2 from India, 4 from Japan, 7 from the Russian Far East, and 9 from China (Chaudhuri et al 2001;Makarchenko et al 2005;Reiss 1988;Sasa & Kikuchi 1995;Wang 2000;Wang & Zheng 1994;Yan et al 2005;Yan & Wang 2006). Yan et al (2005) suggested that 5 Japanese species originally placed in the genus Cryptotendipes by Sasa and his co-authors should be transferred to Demicryptochironomus. Yan and Wang (2006) We also re-examined holotypes of the genus Parachironomus from Japan.…”
Section: Introductionmentioning
confidence: 94%
“…Remarks. Yan et al (2005) suggested that the species should be placed in Demicryptochironomus based on the original description and figures. After re-examining the holotype, we confirm this formally.…”
Section: Demicryptochironomus (Demicryptochironomus) Inawabeceus (Sasmentioning
confidence: 99%
See 3 more Smart Citations